2014
DOI: 10.1080/13607863.2013.875124
|View full text |Cite
|
Sign up to set email alerts
|

The importance of music for people with dementia: the perspectives of people with dementia, family carers, staff and music therapists

Abstract: ObjectivesDespite the popularity of music-based interventions in dementia care, there is a limited knowledge of how and why people with dementia find music beneficial for their well-being. A qualitative study was conducted to develop further insights into the musical experiences of people with dementia and explore the meaning of music in their lives.MethodSeparate focus groups and interviews with (1) care home residents with dementia and their families, (2) day hospital clients with dementia, (3) care home sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
164
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(178 citation statements)
references
References 26 publications
9
164
0
5
Order By: Relevance
“…The most common method of doing this was to play music. The use of music as a tool to soothe agitated individuals has been observed in people with dementia (Janata, 2012;McDermott, Orrell, & Ridder 2014) as well as individuals who have experienced a stroke (Forsblom, Latinen, Särkämö, & Tervaniemi, 2009). Furthermore, Stoudenmire (1975) found that music could have a significant effect on situational anxiety in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The most common method of doing this was to play music. The use of music as a tool to soothe agitated individuals has been observed in people with dementia (Janata, 2012;McDermott, Orrell, & Ridder 2014) as well as individuals who have experienced a stroke (Forsblom, Latinen, Särkämö, & Tervaniemi, 2009). Furthermore, Stoudenmire (1975) found that music could have a significant effect on situational anxiety in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Davidson and Almeida, 2014) might suggest that musical events in a variety of guises still appears to produce similar impacts on those involved. Second, we argue that the inclusion of interviews with family members, clients and nursing staff, all within the context of the same series of performances has enabled this study to address the limitations expressed earlier by McDermott et al, (2014).…”
Section: Resultsmentioning
confidence: 99%
“…As well as exploring the impact of music on specific behaviours, the improvement in the overall wellbeing of those living with dementia is similarly well documented, (Brotons, 2000;McDermott et al, 2013;Sherratt et al, 2004;Sixsmith & Gibson, 2007;and Sung et al, 2012) with further studies exploring the benefits of music on care-givers (Brotons and Marti, 2003;Davidson and Faulkner, 2010;Hammar et al, 2010;McDermott et al, 2014). In particular, music therapy has a long history and association with dementia research (Aldridge, 2000;Kadouchi, 2001;Maroi, 2007;Ridder & Aldridge, 2005;Spiro, 2010) and further work has demonstrated a number of innovative ways of using music in order to enhance the care of individuals with dementia (e.g.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This is a common approach when evaluating the benefit of groups for people with more severe intellectual disabilities, and has also been used to explore the value of music therapy groups. For example, McDermott et al (2014a) recently used the views of staff team members (alongside the views of patients and family members) to explore the benefits of music therapy for people with dementia. Staff were found to view music therapy as an "inclusive social activity for all" (p. 9) and reported music therapy as an enjoyable experience for both themselves and residents.…”
Section: Considerations For Evaluation Of the Groupmentioning
confidence: 99%